Legal Responsibility of Marketplace Platforms for Counterfeit Products Based on Civil Law and ITE Law - Susianto; Kurniawan, Bayu; Setiyawan, Budi; Wibowo, Hary Kesowo; Musruroh, Ainul (LifeSciFi, 2025)
This study explores the legal responsibility of marketplace platforms for the circulation of counterfeit products within the context of civil regulations, the Electronic Information and Transactions Law, and the Consumer Protection Law. The analysis focuses on normative and conceptual principles, aiming to understand how the principles of civil law, the ITE Law, and the Consumer Protection Law synergize to provide effective legal protection for consumers and brand owners. The method used is normative juridical with a statutory and conceptual approach, examining Article 1365 of the Civil Code, Law Number 11 of 2008, in conjunction with Law Number 19 of 2016, and Law Number 8 of 1999, through the study of documents, academic literature, and related regulations. The results indicate that marketplaces have significant legal responsibility to prevent the circulation of counterfeit products through active supervision, notice and takedown procedures, product verification, and transparent internal policies. Negligence in supervision can lead to civil liability, while implementing corporate social responsibility principles strengthens public trust and legal compliance. Strict legal implementation and consistent internal mechanisms are key to creating safe, fair, and sustainable e-commerce. This study provides a normative basis for strengthening online transaction oversight and policy recommendations for marketplaces in Indonesia.